Minimizing Environmental Impacts of Industrial Growth : Case Study of Petrochemical Industry in Kazakhstan - Peszko, Grzegorz (World Bank, Washington, DC, 2013)
Revival and development of the petrochemical industry in Kazakhstan is possible without serious damage to the environment, so long as measures by investors in plant revival include best available techniques (BATs) that avoid and minimize impact on the environment as a whole.This study was initiated to develop methodologies to analyze and mitigate key environmental and natural resource aspects of industrial growth and to propose ways to integrate these methodologies into policy tools. The emerging petrochemical industry was selected to demonstrate how methodology can be applied. The report is structured as two interrelated tools: Technical guidelines (chapters two and three) focus on (i) an analysis of availability of environmental resources in different oblasts; and (ii) references to internationally BATs in the production of polymers. These techniques avoid and minimize impact on the environment as a whole. Policy guidelines (chapters four and five) focus on policy instruments which would encourage plant developers to apply the best available techniques when developing potentially hazardous industrial production in Kazakhstan.